Basic Density of Pinus caribaea Grown in Rubya Plantation, Ukerewe, Tanzania - Mgaywa, Wanjala J.; Sangeda, Anthony Z.; Iddi, Said (Indian Forester, 2019)
Basic wood density of 21 year old Pinus caribaea grown in Rubya forest plantation in Tanzania was determined. Specifically, variation in basic density within a tree and between trees was investigated. A total of 30 defect free trees were randomly selected from which cores were extracted at breast height. Standard procedures for data processing and analysis were followed. The average basic density was 430 kg/m3 (standard deviation = 66 kg/m3). Density variation within trees was statistically significant (p < 0.1) but between trees was not. Density increased from pith to bark and the increase was statistically significant (p < 0.1). The increase from juvenile to transition wood was sharp while from juvenile to mature was fairly gradual. Density decreased with increasing tree diameter. Since the species is suitable for construction, this information is important for foresters in order to control wood quality through silvicultural treatments. It is also recommended that Tanzania Electrical Supply Company may continue to use the species from this plantation for electrical poles to supply electricity in areas where supply of timber with higher densities is limited. These results are therefore important for forest planners, users and policy makers for scaling up planting of the species in the country.